Structure‐Property Relationships of a High Strength Superelastic NiTi–1Hf Alloy. Issue 9 (15th May 2018) - Casalena, Lee; Bucsek, Ashley N.; Pagan, Darren C.; Hommer, Garrison M.; Bigelow, Glen S.; Obstalecki, Mark; Noebe, Ronald D.; Mills, Michael J.; Stebner, Aaron P.
Abstract : The authors report on a relatively new alloy, Ni54 Ti45 Hf1, that exhibits strengths more than 40% greater than those of conventional NiTi‐based shape memory alloys − 2.5 GPa in compression and 1.9 GPa in torsion − and retains those strengths during cycling. Furthermore, the superelastic hysteresis is very small and stable with cycling. Aging treatments are used to induce a very high density of Ni4 Ti3 precipitates, which impede plasticity during cycling yet do not impart substantial dissipation to the reversibility of the phase transformation. Pairing compression testing with high‐energy synchrotron X‐ray diffraction and aberration‐corrected electron microscopy provides an in‐depth look at the structure‐property relationships of this alloy. Specifically, it is found that a combination of small, untwinned retained martensite laths, and dislocations on the austenite‐martensite interfaces primarily strengthen the alloy as opposed to dislocation networks. Furthermore, some combination of nanoprecipitation and interface dislocations is responsible for the remarkably low mechanical hysteresis exhibited by this material. Abstract : Pairing mechanical testing with high‐energy synchrotron X‐ray diffraction and aberration‐corrected electron microscopy provides an in‐depth look at the structure‐property relationships of a relatively new alloy, Ni54 Ti45 Hf1, that exhibits strengtghs more than 40% greater than those of conventional NiTi‐based shape memory alloys − 2.5 GPa in compression and 1.9 GPa in torsion − and retains those strengths during cycling.